Using RSA algorithm for problems of cryptographic protection of information in modern information&telecommunication systems - Жилін, Артем Вікторович; Корнейко, Олександр Васильович; Мохор, Володимир Володимирович (Ukrainian Information Security Research Journal, 2013)
In our time, asymmetric cryptoalgorithms are widely used in solving the problem of cryptographic protection of information, especially in information and communication systems, they include RSA algorithm that has become the most popular. Existing publications mainly reveal the application of RSA algorithm, its primitives in other cryptoalgorithms, analyzing die stability of these cryptosys- tems. Besides, these publications do not provide a comprehensive description of the applications of RSA algorithm. Analyzed sources shows that RSA algorithm and the procedure for its application are described in a number of international, national and industry standards. This article also presents specific examples of using RSA algorithm in the protocols of information and telecommunication systems, and in hardware and software for die realization of cryptographic protection. The analysis shows that despite the appearance of new and more sophisticated asymmetric encryption algorithms in recent years, RSA algorithm is still widely represented in modern information and telecommunication systems to provide cryptographic security problems, including in our country, as it calls for a more detailed study.